THE DEVELOPMENT OF THE MODERN SOCIETY ORDER MOVEMENT IN INDONESIA AND PAKISTAN - Ekawati Ekawati; Yani’ah Wardhani; Fatkhul Mubin (Hikmah: Journal of Islamic Studies, 2022)
AbstractUrban Sufism is a phenomenon that occurs in almost all major cities in the world. In a metropolis environment that is increasingly strongly influenced by postmodern culture, the presence of classes of spirituality is both promising and worrying. On the one hand, the discourse of spirituality becomes the guardian of the "sanctity of the soul". But on the other hand, spirituality is also feared to be trapped in the mechanisms of life of postmodern society. This research is an academic study to determine  the impact of the tarekat movement on people's lives in Indonesia and Pakistan, as well as enrich the  insight into social and diverse life a.  The research method used in this research is a qualitative method carried out through tracing and reviewing information from a number of library materials (library research) and interviews. AbstraksUrban Sufism merupakan fenomena yang terjadi nyaris di segenap kota besar di dunia. Dalam lingkungan masyarakat metropolis yang kian kuat dipengaruhi budaya postmodern, kehadiran kelas-kelas spiritualitas merupakan sesuatu yang menjanjikan sekaligus mengkhawatirkan. Di satu sisi, wacana spiritualitas menjadi penjaga “kesucian jiwa”. Namun di sisi lain, spiritualitas juga dikhawatirkan dapat terperangkap dalam mekanisme kehidupan masyarakat posmodern. Penelitian ini adalah sebuah study akademis untuk mengetahui dampak gerakan tarekat pada kehidupan masyarakat di Indonesia dan Pakistan, serta memperkaya wawasan kehidupan bermasyarakat dan beragama. Metode penelitian yang digunakan pada penelitin ini adalah metode kualitatif yang dilakukan melalui penelusuran dan pengkajian informasi dari sejumlah bahan pustaka (library research) dan wawancara.